2015
DOI: 10.1007/s10964-015-0390-1
|View full text |Cite
|
Sign up to set email alerts
|

The Everyday Implications of Ethnic-Racial Identity Processes: Exploring Variability in Ethnic-Racial Identity Salience Across Situations

Abstract: Given the social and developmental relevance of ethnicity-race during adolescence, it is important to understand the meaning of ethnic-racial identity in adolescents’ everyday lives. The current study considered how individual differences in ethnic-racial identity exploration (i.e., the extent to which individuals have explored their ethnicity-race), and commitment (i.e., the extent which they have a clear sense of what it means to them) influenced variability versus stability in the awareness of ethnicity-rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 54 publications
5
29
0
Order By: Relevance
“…No significant between‐person moderating effects were found for ethnic identity or social support. These null findings may be due to the relatively high mean scores on these measures suggesting ceiling effects or restricted between‐person variability and the limited ability to detect between‐person moderation effects, an issue that has been addressed in prior studies of ethnic identity processes (e.g., Douglass, Wang, & Yip, ; Yip, ).…”
Section: Discussionmentioning
confidence: 99%
“…No significant between‐person moderating effects were found for ethnic identity or social support. These null findings may be due to the relatively high mean scores on these measures suggesting ceiling effects or restricted between‐person variability and the limited ability to detect between‐person moderation effects, an issue that has been addressed in prior studies of ethnic identity processes (e.g., Douglass, Wang, & Yip, ; Yip, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although variability is associated with compromised developmental outcomes in the present study, our other work shows that variability can also promote development for other dimensions of ERI. For example, ethnic/racial minority adolescents who reported more variable awareness of their ethnicity/race (i.e., salience) across situations engaged in greater ERI exploration activities (Wang, Douglass, & Yip, 2016). This promising area of research suggests that the affective (e.g., private regard) versus cognitive (e.g., salience) components of ERI at the level of the specific situation may have important yet different developmental implications.…”
Section: Discussionmentioning
confidence: 99%
“…Although higher mean levels of daily ERI may be associated with a more developed identity status and more positive well-being, variability in daily experiences may be considered a sign of instability and vulnerability. Indeed, prior work on ethnic/racial salience observed that higher variability in salience across situations was associated with lower levels of committing to one's ERI (Douglass et al, 2016). Similarly, research on emotional dynamics has also linked mood variability to poorer psychological well-being in the long term…”
Section: Direct Mediation Of Situational Private Regard: Mean and Varmentioning
confidence: 99%
“…And in the column "Itegel" are published the teachings of Aiyy, ideas of the soul (kut), interviews with traditional healers -Algyschytes, as well as unusual cases from life, traditions, and customs of the Yakuts. Ethnic-racial identity is a multi-faceted construct that captures many different aspects of how individuals make personal sense of their own ethnicity-race [6,7]. So, the main ethnic components are also the headings "Ayannyt" and "Aymakh".…”
Section: Iiidiscussionmentioning
confidence: 99%